CAUSES AND MANAGEMENT OF HIGH FETAL HEAD IN PRIMIGRAVIDAE AT TERM: High Fetal Head in Prmigravidae - Ansari, Asma; Akhtar, Shahida; Aamir, Muhammad (Pakistan Armed Forces Medical Journal, 2008)
Objective: To determine the causes of high foetal head and their relative frequencies in primigravidae presenting at term and to determine the proportion of these patients undergoing lower segment caesarean section or vaginal delivery. Design: A descriptive study. Place and duration of study: The study was carried out at CMH Rawalpindi from April 2002 to March 2003. Patients and Methods: A total of 100 primigravidae patients presenting at term and having a single pregnancy were randomly selected. On the basis of history, Physical examination and abdominal ultrasonography, patients having a high foetal head were recognized and their causes documented. Results: Out of 100 primigravidae, 58 had high foetal head. A discernable cause was found in the 39 (67.2%) patients. Cephalopelvic disproportion (20.7%) and foetal mal position (17.2%) were the leading cause of high foetal head. Lower segment Caesarian section (50%) was the management of choice in half of the patients with high foetal head. Conclusions: Cephalopelvic disproportion and foetal malposition were the major cause of high foetal head in this study and lower segment Caesarean section was the mode of delivery in only 50% of these high risk subjects.